2014
DOI: 10.1186/1471-2334-14-69
|View full text |Cite
|
Sign up to set email alerts
|

Durability assessment results suggest a serviceable life of two, rather than three, years for the current long-lasting insecticidal (mosquito) net (LLIN) intervention in Benin

Abstract: BackgroundLLIN distribution, every three years, is a key intervention of Benin’s malaria control strategy. However, data from the field indicate that LLIN lifespan appears to vary based on both intrinsic (to the LLIN) and extrinsic factors.MethodsWe monitored two indicators of LLIN durability, survivorship and integrity, to validate the three-year-serviceable-life assumption. Interviews with net owners were used to identify factors associated with loss of integrity.ResultsObserved survivorship, after 18 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 14 publications
6
97
1
Order By: Relevance
“…The key LLIN component preventing man-vector contact is the physical integrity [5]. Therefore, the loss of physical integrity represents a major threat for the sleeper and need strong attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key LLIN component preventing man-vector contact is the physical integrity [5]. Therefore, the loss of physical integrity represents a major threat for the sleeper and need strong attention.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 years, 56% of them were removed from their initial households, for different reasons [4]. In addition, rapid physical deterioration of the LLINs was observed 24 months after the distribution, with 90% found with holes [4,5].…”
mentioning
confidence: 99%
“…This study provided compelling information that pyrethroid resistance was developed among the Anopheles populations and may be a serious concern for obtaining sustained efficacy of pyrethroid-based LLINs. The resistant mosquitoes are capable of standing the excito-repellency effect of the LLINs and penetrate through the LLINs to take blood meal from the human sleeping under the net [33]. Failure to take a blood meal reduces the mosquito's longevity, but the resistant mosquitoes are able to feed and are likely to have increased longevity compared to the susceptible mosquitoes.…”
Section: The Development and Spread Of Pyrethroid Resistancementioning
confidence: 97%
“…The damaged and torn LLINs have been shown to increase human-mosquito contact; despite the use of the LLINs, the user received up to five bites per night [3,32]. Gnanguenon et al [33] found that LLIN loss occurred more rapidly than predicted by the 'three-year serviceable life' assumption included in the standards for LLINs as a malaria prevention. The study further suggests that the assumption of three years serviceable life of the LLINs was grossly overestimated and created a situation that could contribute to malaria rebound well before the replacement of the LLINs.…”
Section: The Physical and Biological Integrity Of Llinsmentioning
confidence: 98%
“…Concerns about the effective lifespan of LLINs and a faster than expected deterioration in biological efficacy have been noted in studies in Kenya and Benin [17] [18]. In Laos, another study found that around 40% of impregnated mosquito nets were physically damaged 2 -3 years after use [19]. In Rwanda and Benin, studies have revealed lower life expectancies as against 3 years normally indicated by the manufacturer for both polyethylene and polyester LLINs [11] [20] [21].…”
Section: Introductionmentioning
confidence: 99%